The family practice handbook - Graber, Mark A.; Lanternier, Matthew L. (Mosby, 2001)
Contains the clinical information needed to diagnose and treat disorders commonly seen in family practice. This guide features chapters, a re-organization and information on key topics such as managing anticoagulation, herbal pharmaceuticals, valvular heart disease and more!